Effective pain relief by autologous platelet rich plasma injection in patients suffering from plantar fasciitis - a new thought to culture - Taher, Md Abu; Elahi, Md Nur E; Chowdhury, Md Abul Kalam; Banik, Debasish (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background To date the response of plantar fasciitis (PF) to any treatment is unpredictable. Autologous blood might provide cellular and humoral mediators to induce healing in areas of degeneration at the site of the underlying pathology of plantar fasciitis. Objective This randomized controlled study was designed to compare the effectiveness of local injection of autologous platelet rich plasma (PRP) and local steroid in reducing pain and improving function in patients with plantar fasciitis (PF). Methods The study population comprised two groups; patients of PF treated with steroid injection (n = 15) and patients of PF treated with PRP injection (n = 15). Patients were allocated randomly to receive either a steroid or PRP injections. All patients filled in visual analog scale (VAS) and foot health status questionnaire (FHSQ) for PF at base line and after 6 weeks at follow up. Results PF patients comparison of VAS and FHSQ at base line and 6 weeks after treatment between control group and PRP group showed significant differences for VAS (p = 0.005 and p < 0.001, respectively), and for FHSQ (p = 0.03 and p < 0.001, respectively). While highly significant difference were observed between both groups regarding VAS and FHSQ changes (p = 0.001). Conclusion Local injection of autologous PRP proved to be a promising form of therapy for PF. It is both safe and effective in relieving pain and improving function and superior to local steroids. JBSA 2012; 25(2): 48-53